(untitled) (Journal of Pathology of Nepal, 2014)
Background: Smear cytology has become increasily popular as an alternative to frozen section for the rapid diagnosis of most of central nervous system lesions. The aim of this study was to assess the utility of smear technique for the rapid diagnosis in the neurosurgical biopsies and to compare the smear cytological features with the final histopathological examination. Materials and Methods: This was a prospective study conducted in the Department of Pathology of BP Koirala Memorial cancer Hospital for a period of one year. Sixty cases of clinically suspected CNS tumors were sent for intraoperative smear cytological examination and histological examination. Both techniques were then compared for their ability to diagnose as well as grade the tumors. Results: Gliomas (51.6%) were the most frequently occurring tumors in the total cases. Diagnostic accuracy of squash/smear technique achieved was 88 %( 53/60) when compared with histopathological diagnoses. In two cases, smears comprised of blood clots and no opinion was possible in cytology. Complete discrepancy was seen in five cases that included two cases of atypical meningioma, a one case each of germinoma, glioblastoma and metastatic tumor. Conclusion: Smear technique is a fairly accurate, rapid, easily reproducible and cost effective tool to diagnose brain tumours. Smear cytology is of great value in Intraoperative consultation of central nervous system lesions. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10296 Journal of Pathology of Nepal (2014) Vol. 4, 544-547